Effect Of Economic Growth, Education Level And Human Development Index To Employment Opportunity In North Sumatera Province - Rini Amelia; Ella Silvana Ginting; Apren Halomoan Hutasoit (International Journal on Social Science, Economics and Art, 2021)
The objective of this research is to determine and analyze the effect of Economic Growth, Education level, Human Development Index on Employement Opportunity of North Sumatera Province in 2017–2019. This research use quantitative method secondary data obtained from Badan Pusat Statistik site. Sampel of this research are 33 cities/regencies. The analysis method is using multiple linear regression analysis with panel data by Eviews 10 software. The results of the research show that simultaneously economic growth, education level, and human development index have a significant effect on employement opportunity. Partially, the economic growth and education level don’t have an effect on employement opportunities, while human development index has a negative effect on employment opportunity.